Брокерська діяльність як елемент інфраструктури фондового ринку - Некрасова, О.О. (Управління економікою: теорія та практика, 2025)
Актуальність дослідження обумовлена зростанням інвестиційної активності в Україні. Брокерська діяльність є ключовим елементом інфраструктури ринку цінних паперів, забезпечуючи доступ інвесторів до біржових і позабіржових операцій. Метою статті є аналіз видів та функцій брокерів, порівняння моделей їх роботи на міжнародному ринках, а також виявлення особливостей діяльності. Для досягнення мети використано комплекс методів: аналіз наукових та статистичних джерел, порівняльний аналіз міжнародних брокерів, системний підхід до дослідження регуляторного середовища. Практична цінність дослідження полягає у визначенні переваг та ризиків різних моделей брокерської діяльності, що може бути корисним для інвесторів під час вибору брокера, а також для формування рекомендацій щодо розвитку інвестиційної інфраструктури України. The relevance of the study is determined by the rapid increase in retail investment activity in Ukraine in recent years, which has been accompanied by a significant rise in the number of individual brokerage accounts and trading volumes in foreign securities. Brokerage activity represents a system-forming element of the capital market infrastructure, providing investors with access to both exchange-traded and over-the-counter instruments, contributing to liquidity formation, and reducing information asymmetry between market participants. In the Ukrainian context, where the local market remains underdeveloped and liquidity is limited, global brokerage platforms have become the primary channel for retail investors seeking diversification and participation in international markets.The aim of the article is to analyse contemporary brokerage models, compare their functional capabilities using the example of two global platforms fully available to Ukrainian residents and identify their contribution to enhancing the competitiveness of the national capital market. Particular emphasis is placed on the transformation of brokerage services from traditional order execution to comprehensive digital ecosystems that combine regulatory compliance, advanced technology, analytical tools, and educational support. To achieve this objective, a complex of methods was employed: theoretical analysis of scientific literature and statistical sources, comparative analysis of brokerage platforms across key criteria. The practical value of the research lies in identifying the advantages and risks of different brokerage models, which can assist retail investors in selecting an appropriate broker and serve as a foundation for developing recommendations aimed at improving Ukraine’s investment infrastructure.